The Effects of Combination of Range Motion and Deep Breathing Exercise on Pain in Post-Orthopedic Surgery Patients - Hery Sasongko, - (Publisher Prodi S2 Ilmu Kesehatan Masyarakat Universitas Sebelas Maret, 2019)
Background: Broken bones can cause soft tissue edema, bleeding in the muscles and joints, tendon rupture, damage to nerve tissue and damage to the vasculer and surgery are ways that are carried out to restore the movement function of extremitas and the impact that occurs due to these actions is pain. Acute pain is still found in postoperative non-pathological fracture patients who have received analgesic ketorolac.